Vascular function and structure in the rat aorta - Ng, Keith Wan Kee (Cambridge Scholars Publishing, 2013)
One of the inevitable consequences of ageing is the progressive widening of pulse pressure resulting from stiffening of large arteries. While a large body of literature has been devoted to understanding blood pressure, a parameter proven to be predictive of cardiovascular health, very few books are devoted to explaining arterial stiffening, how it worsens, and why is it important for physicians to consider arterial stiffening when treating resistant hypertension. This book fills this gap. The ...